V.l.n.r. Boot, Bruyning, Priem, A. de Boer, G. Reynders. Staand v.l.n.r. Wolthuis, Hamelink, Spanjer, Van Gelder, Kooker
V.l.n.r. Boot, Bruyning, Priem, A. de Boer, G. Reynders. Staand v.l.n.r. Wolthuis, Hamelink, Spanjer, Van Gelder, Kooker.